Editorial: Homo Virtualis Inaugural Issue - Koskinas, Konstantinos (Homo Virtualis, 2018)
Homo Virtualis is the conception of a humanity of sciences, cultures and socialities powered by the communicative technological innovations. Cyborgs, robots, avatars and virtual communities imagine, construct and create their lives within new technosocial or sociotechnical environments. [...]